The Influence of Energy Intake on The Performance and Endurance of Athletes - Shalma Diva Rismanandi; Linda Riski Sefrina (Poltekkes Kemenkes Mataram, 2022)
Background. Adequate energy intake is an essential component in achieving sports success that plays a role in calorie expenditure, improving and increasing strength, endurance, muscle mass, and health. Many factors can affect each person's immune system, such as genetics, gender, energy intake, age, and nutritional status. Research Methods. the method used in this study is a literature review. A literature search, both international and national, was carried out using the Sinta Indonesia database according to the topic to be discussed by the author. The data obtained were published from 2014-2021. There were 11 articles obtained, 10 of which became material for analysis of the objectives, methods, and interventions, and the results and the suitability of the topics carried out in the research and making of this article. Research Result. it is likely that energy intake will significantly affect the speed, agility, and endurance of an athlete. Conclusion. The effect of energy intake on the performance and strength of the athlete's body can be significantly related depending on the type of exercise performed by the athlete.